SCATTERING AND ABSORPTION OF ARBITRARILY ORIENTED DIPOLES WITH FINITE CONDUCTIVITY - Dominik, H. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Plane wave scattering of lossy dipoles oriented arbitrarily in space is analyzed with the NECAE2 code. Modification of the code allows computing not only the radar cross section but also scattering and absorption cross section. With these electromagnetic characteristics it is possible to describe the relation between reradiated and absorbed power of the scatterer as a function of frequency and conductivity. A comparison with the results obtained with other codes (MININEC, Richmond) shows substantial differences at higher resonances of the dipoles. [Vol. 4, No. 2, pp. 2-15 (1989)]